The Role of Information Quality on the Performance of Hotel Industry in Kenya - Makau, Scholastica; Lagat, Charles; Bonuke, Ronald (European Scientific Journal, ESJ, 2017)
In recent years there have been various studies investigating factors that influence hotel performance in Kenya mostly in coastal region. These studies have analyzed the drivers and factors influencing performance focusing at reasons why some hotels perform outstandingly while other do not. This study focused on how information quality affects the hotel performance. Resource base View theory was used in formulating the study framework. The study adopted a survey design which allowed easy sampling and analysis of data. The Target population was employees of 3 to 5 star rated hotels as classified by Hotel and Restaurants Authority (HRA) as its responses, with a sample of 324 from a population of 9,208 employees. SPSS software was used in analyzing and interpreting data that was collected. The sampling technique used was stratified random sampling. Primary data was collected by use of structured questionnaire instrument and a pilot study was conducted to check for the reliability and validity of the research instruments which were administered through drop and pick method. The results showed that firms need to align their supply chain practices with the level of their information quality in order to achieve enhanced overall business performance. Based on these study findings the researcher concluded that Information Quality has a significantly influenced on hotel Performance to very a great extent. In order for hotel managers to sustain their customer and retain the customer base , there is need to take into consideration on the quality and security of information they make available to their customers as well as their potential customers in order to make right decision e.g. on purchase, price, accommodation, service reservations among other services offered in hotels.